In Vivo and In Vitro Identification of Structural and Sequence Elements of the Human Parechovirus 5′ Untranslated Region Required for Internal Initiation - Nateri, Abdolrahman S. (American Society for Microbiology, 2000)
Sequence analysis of the picornavirus echovirus 22 led to its classification as the first member of a new genus, Parechovirus, and renaming as human parechovirus type 1 (HPeV1). Although distinct from other genera in most of the genome, the 5′ untranslated region (5′UTR) shows similarities to that of cardio/aphthoviruses in some of its structural domains (A to L). The 5′UTR plays an important role in picornavirus translation initiation and in RNA synthesis. To investigate translation in HPeV1, we engineered an extensive range of mutations (including precise deletions and point mutations) into the 5′UTR. Their effects were studied both by in vitro transcription-translation using a bicistronic construct and by in vivo studies using an infectious, full-length HPeV1 cDNA. These approaches allowed the HPeV1 internal ribosome entry site (IRES) to be mapped. Deletions within the first 298 nucleotides had little impact in the in vitro system, while deletions of nucleotides 298 to 538 had a significant effect. Precise removal of domains H and L (nucleotides 287 to 316 and 664 to 682, respectively) did not significantly reduce translation efficiency in vitro, while domains I, J, and K (nucleotides 327 to 545, 551 to 661, and 614 to 645, respectively) appeared to have much more important roles. Mutation of a phylogenetically conserved GNRA motif (positions 421 to 424) within domain I severely reduced translation. We also confirmed the identity of the AUG (positions 710 to 712) which initiates the open reading frame, the positive identification of which has not been possible previously, as the N terminus of the polyprotein is blocked and not amenable to sequence analysis. This is therefore important in understanding parechovirus genome organization. Mutation of the AUG or an upstream polypyrimidine tract leads to aberrant translation, suggesting they both form part of the parechovirus Yn-Xm-AUG motif. In vivo experiments confirmed the importance of domains I, J, and K, the conserved GNRA motif, polypyrimidine sequences, and AUG, as mutations here were lethal. These features are also important in the IRES elements of cardio/aphthoviruses, but other features reported to be part of the IRES of some members of these genera, notably domains H and L, do not appear to be critical in HPeV1. This adds weight to the idea that there may be functional differences between the IRES elements of different picornaviruses, even when they share significant structural similarity.